Ch. 249, Subchapter 5-Crimes against the Person, §§ 142 & 151 in 1909, Wash. Sess. Laws 929, 931-33 (1909 E. L. Boardman). - (:unkn) unknown (My University, 1909)
Every person who shall fight or participate in, as second or assistant, any duel within this state, in which any person is killed, or who, by previous appointment made within this state, shall fight or participate in, as second or assistant, any duel out of the state, in which any person is killed, shall be guilty of murder in the second degree; and, in the latter case, may be proceeded against in any county in this state...Every person who shall make or keep gun powder, or any other explosive substance, in a city or village, in any quantity or manner prohibited by law or by ordinance of such municipality, if an explosion thereof shall occur whereby the death of a human being is occasioned, shall be guilty of manslaughter."
Keywords: DUELING; TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER